2022
DOI: 10.1002/jum.16069
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Structural Anomaly Among Singletons and Twins

Abstract: Objectives This study was designed to reveal structural abnormalities in singleton and twin pregnancies in the Chinese population. Methods This retrospective study spanned 8 years and included 1228 singleton pregnancies (112,919 examinees) and 49 twin pregnancies (1865 examinees) with structural anomalies diagnosed by ultrasound. Detailed descriptions of anomalies, gestational weeks at diagnosis, and maternal age were recorded. The odds ratio was evaluated in twin pregnancies with detectable structural anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Most often, fetuses are discordant for anomalies, even in monozygotic gestations. A 2023 retrospective study by Ting et al 6 evaluated 1865 twin pregnancies in China and reported that of the twin pregnancies affected by structural anomalies, 92% involved one fetus and 8% involved both fetuses. These results were similar to Boyle et al, 5 who reported that 11% of twins with a structural anomaly affected both twins.…”
Section: Discordance For Structural Anomaliesmentioning
confidence: 99%
“…Most often, fetuses are discordant for anomalies, even in monozygotic gestations. A 2023 retrospective study by Ting et al 6 evaluated 1865 twin pregnancies in China and reported that of the twin pregnancies affected by structural anomalies, 92% involved one fetus and 8% involved both fetuses. These results were similar to Boyle et al, 5 who reported that 11% of twins with a structural anomaly affected both twins.…”
Section: Discordance For Structural Anomaliesmentioning
confidence: 99%